Efficacy of quantitative diffusion MR imaging for the differentiation of malignant and benign lung lesions - Cihan Şimşek; Necdet Poyraz (Van Tıp Dergisi, 2019)
INTRODUCTION: To assess lung lesions with quantitative diffusion MR imaging. METHODS: We retrospectively evaluated 120 patients with pulmonary lesions undergoing diffusion-weighted MR imaging. The ADC values of lung lesions were calculated and correlated with biopsy results. RESULTS: The ADC of benign lung lesions (2.03+-0.09x10-3mm2/s) was significantly higher (P<0.001) than that of malignant lung tumors (1.11+-0.25x10-3mm2/s). Selection of 1.37x10-3mm2/s as a cut-off point for differentiating malignant from benign lung lesions revealed an area under the curve of 0.94, an accuracy of 87.5 %, a sensitivity of 94.9 %, and a specificity of of 73.1%. DISCUSSION AND CONCLUSION: Quantitative diffusion MR imaging may be used for differentiation of benign from malignant lung tumors.